Self-interference of split HOLZ line (SIS-HOLZ) for z-dependent atomic displacement measurement: Theoretical discussion. (June 2017) - Norouzpour, Mana; Rakhsha, Ramtin; Herring, Rodney
Abstract : Highlights: Detailed analytical proofs of the self interference of split HOLZ (SIS-HOLZ) line technique are presented. Three different atomic displacement profiles (i.e., V-shape, Bell-shape, and Parabola) are studied and their corresponding phase profiles are generated. Phase sensitivity is studied for the phase profile across the split HOLZ line, diffracted from a Bell-shape strained specimen. Abstract: A characteristic of the majority of semiconductors is the presence of lattice strain varying with the nanometer scale. Strain originates from the lattice mismatch between layers of different composition deposited during epitaxial growth. Strain can increase the mobility of the charge carriers by the band gap reduction. So, measuring atomic displacement inside crystals is an important field of interest in semiconductor industry. Among all available transmission electron microscopy techniques offering nano-scale resolution measurements, convergent beam electron diffraction (CBED) patterns show the highest sensitivity to the atomic displacement. Higher Order Laue Zone (HOLZ) lines split by small non-uniform variations of lattice constant allowing to measure the atomic displacement through the crystal. However, it could only reveal the atomic displacement in two dimensions, i.e., within the x – y plane of the thin film of TEM specimen. The z -axis atomic displacement which is along the path of the electron beam has been missing. This information can be obtained by recovering the phase information across the split HOLZ line using the self-interference of the split HOLZ line (SIS-HOLZ). In this work, we report the analytical approach used to attain the phase profile across the split HOLZ line. The phase profile is studied for three different atomic displacement fields in the Si substrate at 80 nm away from its interface with Si/Si0.8 Ge0.2 superlattices.